Establishing the Key Outcomes for Pediatric Emergency Medical Services Research. (8th November 2018) - ,; Adelgais, Kathleen M.; Hansen, Matthew; Lerner, E. Brooke; Donofrio, J. Joelle; Yadav, Kabir; Brown, Kathleen; Liu, Yiju T.; Denslow, Paula; Denninghoff, Kurt; Ishimine, Paul; Olson, Lenora M.
Abstract: The evidence supporting best practices when treating children in the prehospital setting or even the effect emergency medical services (EMS) has on patient outcomes is limited. Standardizing the critical outcomes for EMS research will allow for focused and comparable effort among the small but growing group of pediatric EMS investigators on specific topics. Standardized outcomes will also provide the opportunity to collectively advance the science of EMS for children and demonstrate the effect of EMS on patient outcomes. This article describes a consensus process among stakeholders in the pediatric emergency medicine and EMS community that identified the critical outcomes for EMS care in five clinical areas (traumatic brain injury, general injury, respiratory disease/failure, sepsis, and seizures). These areas were selected based on both their known public health importance and their commonality in EMS encounters. Key research outcomes identified by participating stakeholders using a modified nominal group technique for consensus building, which included small group brainstorming and independent voting for ranking outcomes that were feasible and/or important for the field.